The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1161/jaha.113.000588
|View full text |Cite
|
Sign up to set email alerts
|

Need for Prophylactic Application of Verapamil in Transradial Coronary Procedures: A Randomized Trial

Abstract: BackgroundVerapamil is traditionally applied prophylactically in transradial procedures to prevent radial artery spasm. However, verapamil may have side effects and is contraindicated in some clinical settings.Methods and ResultsDuring an investigator‐initiated, randomized, double‐blind trial, we evaluated the need for preventive verapamil administration. After vascular access was established, patients received either 5 mg verapamil (n=297) or placebo (n=294). We compared the rate of access site conversions as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Moreover, the "is Verapamil In TransRadial Interventions OmittabLe?" (VITRIOL) trial showed similar access site conversion rates and/or spasmolytic administration rates between the prophylaxis and placebo groups, suggesting that preventive use of verapamil may not be necessary [14]. Applying warmth to the forearm may be helpful in relieving the spasm.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the "is Verapamil In TransRadial Interventions OmittabLe?" (VITRIOL) trial showed similar access site conversion rates and/or spasmolytic administration rates between the prophylaxis and placebo groups, suggesting that preventive use of verapamil may not be necessary [14]. Applying warmth to the forearm may be helpful in relieving the spasm.…”
Section: Discussionmentioning
confidence: 94%
“…Nitroglycerin is also contraindicated in patients with significant aortic stenosis, hypotension, and cardiogenic shock. Furthermore, a recent study indicated that beyond the learning curve preventive administration of intra-arterial verapamil offers no advantage over ad hoc application in terms of access site conversion rates [20]. In our center, in appropriate cases, a bolus of intra-arterial nitroglycerin and/or intra-arterial verapamil is given prophylactically.…”
Section: Discussionmentioning
confidence: 97%
“…In a head-to-head comparison study between nitroglycerin and verapamil there was no statistically significant difference in the ACEI -angiotensin converting enzyme inhibitor; BP -blood pressure; HDL-C -high-density lipoprotein-cholesterol; LDL-C -low-density lipoprotein-cholesterol; RAS -radial artery spasm incidence of RAS [22]. Furthermore, a recent study indicated that beyond the learning curve preventive administration of intra-arterial verapamil offers no advantage over ad hoc application in terms of access site conversion rates [23]. It was also reported that 72.2% of Japanese operators do not use any medication for spasm prophylaxis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study indicated that beyond the learning curve preventive administration of intra-arterial verapamil offers no advantage over ad hoc application in terms of access site conversion rates [23]. It was also reported that 72.2% of Japanese operators do not use any medication for spasm prophylaxis [23]. In keeping with these recent reports, the preventive use of vasodilators may not be mandatory, especially in centres with high-volume transradial catheterisation.…”
Section: Discussionmentioning
confidence: 99%